Local Election Administrators in the United States
XXVIII, 334 p. 42 illus., 19 illus. in color.
Keywords: This book focuses on the more than 8,000 local elections administrators in counties, municipalities, and townships who largely manage the key administrative processes of elections, work with campaigns and candidates, design voting materials and choose voting equipment, staff early, and Election Day polling locations, and communicate with and educate voters. They are the frontline of democracy, and this is the first book that explores who becomes an election administrator; their opinions about election reform and election integrity; how LEOs responded to the unique challenges of the 2020 election which included misinformation and even death threats; and how to move forward to ensure a sustainable, diverse, and sustainable community. Paul Gronke is Professor of Political Science and Director of the Elections & Voting Information Center at Reed College, USA. David Kimball is Professor and Chair of Political Science, University of Missouri at St Louis, USA. Thessalia Merivaki is Associate Teaching Professor, McCourt School of Public Policy, and Associate Research Professor, Massive Data Institute, Georgetown University, USA Mara Suttmann-Lea is Associate Professor of American Politics in the Department of Government and International Relations at Connecticut College. Christian Grose is Professor of Political Science and Public Policy in the Department of Political Science and International Relations at the University of Southern California, USA Bridgett King is Associate Professor in the Department of Political Science at the University of Kentucky, USA.